A Large-Area Smart Window with Tunable Shading and Solar-Thermal Harvesting Ability Based on Remote Switching of a Magneto-Active Liquid - Heiz, Benjamin P. V.; Pan, Zhiwen; Su, Lingqi; Le, Si Thien; Wondraczek, Lothar (Advanced Sustainable Systems, 2018)
Switchable windows provide intriguing opportunities for addressing the challenges of modern building skins. In particular, indoor comfort and the control of radiative heat transfer into and out of the building require adaptive and tunable solutions for shading and emissivity. Here, a switchable, ultrathin suspended particle device (SPD) for large-area integration with smart facades is presented. The system is based on a fluidic window, manufactured at low cost from a laminate of structured, rolled glass and a thin cover with high surface strength. Loading the circulating fluid with magnetic nanoparticles enables active shading and solar-thermal energy harvesting, whereby the loading state and, hence, the optical properties of the liquid can be controlled through remote switching in a particle collector-suspender device. In the fully shaded state, a typical harvesting efficiency of 45% of the incoming solar power is obtained. For an average solar irradiance of 1000 W m−2 during 800 h a−1, this corresponds to a solar thermal harvesting capacity in the range of 360 kWh a−1 m−2. In comparison to alternative SPD concepts, this enables high flexibility and compatibility with established production lines. In addition, there is no need for further electrical contact, transparent conductive layers, or electrolytes.
CRIS-Team Scopus Importer:2023-04-20
Keywords: energy efficient buildings; energy harvesting; fluidic window; glass; magnetic properties; nanoparticles; smart windows; solar energy